Correlates of transfusion transmissible infections among patients with sickle cell disease in Nigeria: case-control study. Issue 4 (4th July 2022) - Akpa, Onoja; Babalola, Oluwatoyin; Odetunde, Abayomi; Fagbamigbe, Adeniyi; Fasola, Foluke; Brown, Biobele; Alamukii, Nanfizat; Babalola, Chinedum; Odaibo, Georgina; Falusi, Adeyinka
ABSTRACT: Transfusion transmissible infections (TTIs) such as Hepatitis B Virus (HBV), Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV) are among the most frequent complications in individuals with Sickle Cell Disease (SCD). We investigated factors associated with TTIs in SCD patients and controls in South-west Nigeria. A total of 2, 034 participants with or without SCD were recruited in a matched case-control study. HIV, HBV and HCV infections were diagnosed using commercialy available ELISA kits (Biorad, Paris). Samples positive for HIV ELISA were further confirmed using Western blot. Data were analyzed using descriptive statistics, paired/independent t-test and logistic regression at p = .05. Proportion with HBV was higher among those with multiple sexual partners (12.7%), tattoo/body incision (11.8%), and sharing of sharp objects (7.3%), but HIV was only higher among participants with history of tattoo/body incision (1.5%). Prevalence of TTIs was similar among participants with or without transfusion. History of sharing sharp objects (adjusted odds ratios (aOR) = 1.72; 95%CI:1.11–2.66) and tattoo/body incision (aOR = 1.89; 95%CI:1.22–2.94) almost doubled the risk of HBV. TTIs are endemic in the studied area. Certain lifestyles predispose people to TTIs than having blood transfusion. Population-based intervention targeting lifestyle changes may reduce the risk of TTIs in the study area. Abbrveviations AA: Hemoglobin AA; AC: Hemoglobin AC; aOR: adjusted Odds Ratios; AS: Hemoglobin AS; CHOP: Children Outpatient; CI: Confidence Interval; EDTA: Ethylenediamine Tetraacetic Acid; GOP: General Outpatient; HBV: Hepatitis B Virus; HCV: Hepatitis C Virus; HIV: Human Immunodeficiency Virus; HPLC: High Performance Liquid Chromatography; IAMRAT: Advanced Medical Research & Training; IDU: Injection Drug Use; MOP: Medical Outpatient; SC: Hemoglobin SC; SCD: Sickle cell disease; SD: Standard Deviation; SF: Hemoglobin SF; SS: Hemoglobin SS; STDs: Sexually Transmitted Diseases; TTI: Transfusion transmissible infections; UCH: University College Hospital Ibadan; UI: University of Ibadan;